The effects of cooking salmon sous-vide on its antithrombotic properties, lipid profile and sensory characteristics. (January 2021) - Redfern, Shane; Dermiki, Maria; Fox, Shelley; Lordan, Ronan; Shiels, Katie; Kumar Saha, Sushanta; Tsoupras, Alexandros; Zabetakis, Ioannis
Graphical abstract: Highlights: Mild sous-vide cooking beneficially preserved the antithrombotic potency of salmon PL. Salmon PL MUFA and n-3 PUFA levels were not affected by mild sous-vide conditions. Higher temperatures reduced antithrombotic properties and levels of EPA and PUFA. n-6/n-3 PUFA ratio of salmon PL remained at beneficial low levels during sous-vide. Sous-vide preserved salmon cardioprotective properties and sensory characteristics. Abstract: Fish contains bioactive polar lipids (PL) and is mainly consumed cooked. The aim of this study was to evaluate the sensory characteristics of sous-vide cooked salmon and the in vitro cardio-protective properties of its PL. PL were extracted from brined and un-brined sous-vide preparations in 52 °C, 65 °C, and 80 °C, while their antithrombotic cardio-protective properties were assessed in human platelets and their fatty acid (FA) content was evaluated by LC-MS. Sensory tests were performed using napping followed by check-all-that apply (CATA). Mild temperatures (52 °C, 65 °C) did not affect the inhibitory effect of PL from brined and un-brined salmon, against human platelet aggregation induced by platelet-activating factor (PAF), thrombin, adenosine diphosphate (ADP) or collagen. In higher temperatures used for pasteurization (80 °C), a reduction of antithrombotic properties was observed in PL from both un-brined and brined salmon samples. This reduction was accompanied by a decrease of their n3 eicosapentaenoic acid (EPA) and overall polyunsaturated FA (PUFA) content, but only in the PL of the un-brined salmon preparations. Thus, changes in the fatty acid content of PL of all sous vide salmon preparations, and especially of specific PUFA, seem to be associated with the observed changes in their antithrombotic potency. Changes in the content of the n-3 docosapentaenoic acid (DPA), a precursor of EPA and docosahexaenoic acid (DHA), seem to be associated with differences observed in the antithrombotic potency of PL from different sous vide salmon preparations. Taste attributes were not affected by the conditions of sous-vide preparations, whereas slight textural differences were observed in samples treated at 65 °C and 80 °C. These outcomes, if combined with the observed low values of the n-6/n-3 PUFA ratio in PL of all sous-vide preparations, further suggest a beneficial role for such a mild cooking procedure for preserving the antithrombotic and cardio-protective properties of salmon without affecting its sensory characteristics.